A Borges Review on Tango - Espitia Cabrejo, Néstor; Becerra Mayorga, Witton (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The bond between Borges and tango is very close. His vision about this music is related to the experiences he lived while tango started to spread and succeed in Argentina. This paper is a literature review of Borges’ relationship with tango. The main purpose of this revision is to understand the collaboration between Borges and Astor Piazzolla (1921-1992) in 1965. The last section of the paper is preceded by an analysis of Borges’ tango mythical vision. The approach to this literature review is shaped by the bibliography that focuses on Borges and tango, as well as the works which study the relationship between Borges and Piazzolla. Borges’ idea of tango is attached to the tradition which creates milonga as a rural music style. This music when it arrived in Buenos Aires was enriched with oral tradition and popular culture. This literature review reveals that Borges preferred the mythical vision of tango instead the innovation. The connection between tango and Borges presented here is the basis to reconsider the result of Borges and Piazzolla’s collaboration. It also contributes to the study between music and literature by the Argentinian author. Moreover, it is the foundation to elaborate a new approach with respect to tango.